Building a National Gallery for Ireland: an architectural analysis - Buckley, Aoife-Marie (Trinity College Dublin. School of Histories & Humanities. Discipline of History Of Art, 2026)
This thesis is a history of the architecture of the National Gallery of Ireland, from 1852 to 2002. An assemblage of four wings - the Dargan, Milltown, Beit, and Millennium - its architecture has not been examined in-depth, nor the complex development of its architecture been studied previously. This thesis examines the span of the Gallery's significant architectural evolutions through three frames - context, design, and nationality. Nestled within the cultural quarter of Dublin, the thesis situates the genesis of the Gallery and each subsequent development in this context in its respective period. It investigates their particular design lineages, identifies the designer in each and presents them in tandem with other key design-participants within a wider web of design process. By means of this process of tracing, this thesis looks for notions of nationality ideated in the building fabric. It employs a building-centred historical approach, through spatial, situated-spatial, visual, and textual analysis. This thesis makes an original contribution to the wider understanding of the National Gallery of Ireland by narrating a comprehensive architectural history of the national cultural institution in its many complexities. It constitutes the only such history of a purpose-built national cultural institution in Ireland.
APPROVED
Keywords: Thomas Manly Deane; Beit Wing; Milltown Wing; Countess Milltown; Russborough House; Thomas Bodkin; Exhibition of Art-Industry; Walter Armstrong; George Francis Mulvany; Benson and Forsyth; National Gallery of Ireland; Leinster Lawn; Royal Dublin Society; Irish Institution; Dargan Committee; William Dargan; Dargan Wing; Irish Industrial Exhibition; 1853; Irish National Gallery; South Kensington Complex; Francis Fowke; Richard Griffith; Cork Industrial Exhibition; Millennium Wing; Architectural Competition; Office of Public Work; National Cultural Institution; 1903; 2002; 1968; Uinseann Mac Eoin; John Skipton Mulvany; Charles Lanyon; Frederick Claredon; Natural History Museum; National Style; Stapleton Plaster; Cultural Cluster; Dublin Cultural Cluster